The Role of Education in Moderating the Effects of Income and Consumption on Financial Welfare among Agricultural Families - Fitrianingsih, Diana; Mardiana, M. (Golden Ratio of Finance Management, 2025)
Sustainable development is essential for enhancing family financial welfare, particularly in rural agricultural communities. This study investigates the influence of income and consumption patterns on family financial welfare, with education level as a moderating variable, focusing on maize farming households in Wajak Subdistrict, Malang Regency. Adopting a quantitative cross-sectional approach, data were collected from 237 purposively selected maize farmers through structured surveys. Partial Least Squares (PLS) analysis was employed to evaluate the relationships among variables. The results reveal that income has a positive and significant effect on financial welfare, indicating that higher earnings enhance economic stability. Consumption patterns also significantly affect financial welfare, emphasizing the role of effective financial management. Education is found to moderate the relationship between income and financial welfare, where higher education improves resource management and financial decision-making. However, it does not moderate the link between consumption patterns and financial welfare, suggesting that such patterns are shaped more by contextual economic and social factors. These findings underscore the importance of financial literacy and structured planning in promoting sustainable welfare among agricultural families.